How Pre-service Teachers' Conceptions of Assessment Change Over Practicum: Implications for Teacher Assessment Literacy - Xu, Yueting; He, Liyi (Frontiers in Education, 2019)
Practicum poses great challenges for pre-service teachers who learn to assess because their conceptions of assessment (CoA) may undergo dramatic changes. This multiple case study reports on how three pre-service teachers’ CoA changed over practicum at a primary school in China. Findings show that pre-service teachers’ CoA have experienced a rapid change from a superficial perception of assessment for academic achievement and moral character development, to a more comprehensive understanding of varied assessment purposes, constructs in assessment criteria, feedback, fairness in classroom assessment, and students’ involvement in and engagement with assessment. A range of factors are found to have exerted varying degrees of influence on these conception changes, such as personal factor (i.e., agency in assessment), experiential factors (i.e., school-based assessment practices, interactions with students, and (anti-)apprenticeship of observation about assessment) and contextual factors (i.e., mentoring, classroom reality, school assessment culture, and national assessment policy). These findings are discussed in terms of how these changes are diverse but limited, as well as how the mediating factors have exerted differentiated influences in positive or negative ways. This paper concludes with implications for research on teachers’ CoA and professional development for assessment literacy.